DIGITAL ENTREPRENEURIAL KNOWLEDGE AND ALERTNESS AS PREDICTORS OF BUSINESS EDUCATION STUDENTS’ DIGITAL ENTREPRENEURIAL INTENTION IN EDO STATE - EDIAGBONYA, KENNEDY; ALONTA, GABRIEL CHIDIEBERE; ANI , BENJAMIN ONABULU (Sokoto Educational Review, 2025)
The increasing level of unemployment amongst graduates and non-graduates in this digital age is giving serious concern to stakeholders and this has informed this study. The purpose of this study was to ascertain the extent to which digital entrepreneurial knowledge and alertness predict business education students’ digital entrepreneurial intention in Edo State. A total of 382 students of business education from the University of Benin, Benin City and Ambrose Alli University, Ekpoma participated in the study. The "Digital Entrepreneurial Knowledge, Alertness and Digital Entrepreneurial Intention Questionnaire (DEKADEIQ)" was the instrument used to collect data. The Cronbach Alpha was used in ascertaining the reliability and each of the sub-scales yielded the following: digital entrepreneurial alertness (.912); digital entrepreneurial knowledge (.850) and digital entrepreneurial intention (.804). The Pearson Product Moment Correlation and simple linear regression analysis were used for the analysis. According to the results, digital entrepreneurial knowledge significantly predicted business education students’ digital entrepreneurial intention in Edo State (R2 = .823, F (1, 242) = 1124.178, P <. 05, t = 33.529, ? = .977, SE = .029). Digital entrepreneurial alertness significantly predicted business education students’ digital entrepreneurial intention in Edo State (R2 = .957, F (1, 242) = 5379.193, P <. 05, t = 73.343, ? = .519, SE = .007). The study therefore recommends that stakeholders should give emphasis on digital entrepreneurship in the face of this digital age.